The theoretical analysis of mass and energy flow through solar collector - chimney system = Analiza teoretyczna przepływu masy i energii przez układ kolektor słoneczny - komin - Lipnicki, Zygmunt; Gortych, Marta; Staszczuk, Anna; Kuczyński, Tadeusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The goal of the paper was to simplify the designing process for mass and energy flow through solar collector - chimney system. Theoretical analysis allowed to get involved system of three nonlinear analytical equations in dimensionless forms that have been saved. Dimensionless numbers for the problem are well known in the literature on fluid mechanics and thermodynamics: Reynolds, Grashof, Galileo, Biot and Prandtl.
Keywords: solar collector; chimneys; air flow; analytical solution; kolektor słoneczny; komin; przepływ powietrza; analiza teoretyczna